PENGARUH PERDAGANGAN INTERNASIONAL TERHADAP PERTUMBUHAN EKONOMI INDONESIA - Nurhayati Nurhayati; Hijri Juliansyah (LPPM Universitas Malikussaleh – Indonesia, 2023)
This study examined the `effect `of `exports, `imports, exchange rates, `and `domestic investment to economic growth in Indonesia. This study used secondary `data `from 2000 to 2019. The `data `analysis technique used was multiple linear regression models (Time Series) with `the `help `of Eviews 10. The results partially indicated that export, import, exchange rate, and PMDN activities did not influence economic growth in Indonesia. However, simultaneously, export, import, exchange rate, and PMDN activities positively and significantly influenced economic growth in Indonesia. The coefficient of determination of R2 `in `this `study was 0.831, meaning `that exports, imports, exchange rates, and PMDN were 0.609173 or 60.9%, which were declared to have no effect, and the remaining 39% was stated not to be `influenced `by other variables `outside of this study.